The use of autonomous underwater vehicles for monitoring aquaculture setups in a high-energy shallow water environment: case study Belgian North Sea - Peck, Christopher J.; Langedock, Kobus; Boone, Wieter; Fourie, Fred; Moulaert, Ine; Semeraro, Alexia; Sterckx, Tomas; Geldhof, Ruben; Groenendaal, Bert; Ponsoni, Leandro (Frontiers in Marine Science, 2024)
Effective and frequent inspections are crucial for understanding the ecological and structural health of aquaculture setups. Monitoring in turbid, shallow, and dynamic environments can be time-intensive, expensive, and with a certain level of risk. The use of monitoring techniques based on autonomous vehicles is an attractive alternative approach because these vehicles are becoming easier to use, cheaper and more apt to carry different sensors. In this study, we used an Autonomous Underwater Vehicle (AUV) equipped with interferometric side scan sonar to observe an aquaculture setup in the Belgain North Sea. The surveys provided information on the longlines and indicated that the mussel dropper lines touched the seabed, implying that mussel growth weighed the longlines down. The side scan imagery also captured significant scouring around the longline anchors and localised debris on the seabed, which is important information to ensure the long-term sustainability of the setup and impact on the seabed. The results show that observing mussel longlines in a turbid, shallow, and high-energy environment using an AUV is a viable technique that can provide valuable information. Thus, the present study provides key insights into the application of innovative uncrewed monitoring techniques and forms an important step towards efficient and sustainable management of offshore aquaculture setups.